L’oggetto della pedagogia: la differenza generazionale - Casale, Rita (Studi sulla Formazione/Open Journal of Education, 2023)
Taking into account the historical interdisciplinary epistemological matrix of the science of education, while at the same time considering the social and cultural importance of pedagogical questions as well as the scarce academic and public resonance of the scientific, theoretical and historical research of pedagogues, the article first highlights the need to determine the specific object of pedagogy. It then proposes, on the basis of a tradition that goes back to Friedrich Schleiermacher and a series of educational philosophers such as Siegfried Bernfeld, Walter Benjamin, Hannah Arendt, Alexander Mitscherlich and Micha Brumlik, to consider (inter)generational relationships in their multiple variations (parent-child, teacher-pupil, teacher-student and adolescent-adult relationships) as the core of the science of education.